Design and Build a RESTful API Based Data Integration System - Pratama, Muhammad Fikri; Andriyanto, Teguh; Wardani, Anita Sari (Nusantara of Engineering (NOE), 2025)
Data and information are important elements in determining the success of an entity in a government agency, especially in the current era of digital competition. Every activity carried out by a government agency produces data that becomes physical evidence of the implementation of the activity. Even though the data is available in government agency systems, challenges arise when the data needs to be processed. The search process becomes difficult and a lot of time is wasted because the amount of data is limited by technological devices. Data and information management is a key aspect in determining accountability in every activity carried out. To overcome this problem, the government issued a policy through Presidential Regulation no. 39 of 2019 concerning One Indonesian Data. This policy aims to regulate the governance of data produced by government agencies, both central and regional, to support development planning, implementation, evaluation and control. This research aims to design an information system that is able to integrate data from various different information systems using RESTful APIs. The research methods used include needs analysis, system design, and implementation. The research results show that creating web-based applications using RESTful APIs facilitates data communication between systems, ensures the availability of clear data, and meets the public data needs of the community.